2006
DOI: 10.1088/0953-8984/18/42/011
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional electron transport and thermopower in an individual InSb nanowire

Abstract: We have measured the electrical conductance and thermopower of a single InSb nanowire in the temperature range from 5 to 340 K. Below temperature (T) 220 K, the conductance (G) shows a power-law dependence on T and the current (I)-voltage (V) curve follows a power-law dependence on V at large bias voltages. These features are the characteristics of one-dimensional Luttinger liquid (LL) transport. The thermopower (S) also shows linear temperature dependence for T below 220 K, in agreement with the theoretical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…7 Therefore, the higher thermopower of our nanowires compared with that measured in Ref. 4 can arise because of larger electron-electron interaction.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…7 Therefore, the higher thermopower of our nanowires compared with that measured in Ref. 4 can arise because of larger electron-electron interaction.…”
Section: Discussionmentioning
confidence: 64%
“…Among these structures, electronic properties of quasi-one-dimensional wires are of special interest because the enhanced electron-electron interaction results in the formation of the unusual state of the electronic subsystem called a Luttinger liquid. 1 The characteristic features of the transport properties of a Luttinger liquid were revealed in experimental results on electrical conductance and current-voltage characteristics of InSb, [2][3][4] Bi 1Àx Sb x , 5 NbSe 3 , 6 and MoSe nanowires 7 ; polymer nanofibers 8 ; carbon nanotubes [9][10][11] ; and fractional quantum Hall edge states. 12 Luttinger liquid behavior of the thermoelectric power was revealed in InSb nanowires 3,4 and carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly different thermopower with an opposite sign was also reported for bismuth nanowires with a diameter of 150-480 nm in comparison with bulk bismuth [67]. Theoretical predictions by Mingo [33] showed InSb as an excellent thermoelectric material with a large figure of merit for a nanowire with a diameter around 20 nm, but when Zhou et al [58] found that the thermopower of a 40 nm wire did not increase even relative to bulk InSb. This discrepancy was attributed to phonon effects or energy spectrum dispersion near the Fermi level.…”
Section: Discussionmentioning
confidence: 88%
“…Subsequently, gold (or Pt) electrical contacts are fabricated using photolithography and electron beam evaporation. One of the electrodes acts as a heater, and Joule heating through a heater line is used to establish a temperature difference which generates a thermoelectric voltage in the nanowire [56][57][58]. The Seebeck coefficient of the nanowire is calculated using ΔT and measuring the Seebeck voltage.…”
Section: S T Ztmentioning
confidence: 99%